A model-based rear-end collision avoidance algorithm for heavy commercial road vehicles. (April 2015) - Rajaram, Vignesh; Subramanian, Shankar C
A rear-end collision is one of the most frequent accidents occurring on roadways. In this paper, a model-based longitudinal collision avoidance algorithm is developed for heavy commercial road vehicles to avoid rear-end collisions. This paper focuses on the inclusion of the dynamics of the pneumatic brake system in the collision avoidance algorithm. The developed algorithm also considers the dynamic behaviour of the heavy vehicle during braking such as the dynamic load transfer, the dynamic brake force distribution between the wheels and the maximum traction available at the tyre–road interface. The pressure transients in the brake chamber are modelled as a linear first-order dynamic system with a time delay. Commercially available vehicle dynamic simulation software, TruckSim, is used for simulating the developed control algorithm for realistic traffic scenarios with different loading and road conditions. The results obtained from the simulations are compared with the experimental results obtained from a hardware-in-the-loop system and the simulation results are found to be promising.